Formulasi Dan Uji Aktivitas Antibakteri Gel Ekstrak Etanol Daun Brotowali (Tinospora cordifolia (Willd.) Miers) Terhadap Bakteri Pada Ulkus Diabetikum - Meutia , Rena; Valerie , Monica; Safriani , Riri; Aiman , Hanifa Rifdah; Fachrunniza , Yunda; Fadhilah , Dhea Nur; Ratmelya , Dara Sukma; Sabrina , Nur Irhamni; Meila , Okpri (Journal of Pharmaceutical and Sciences, 2026)
Diabetic ulcers are a chronic complication of Diabetes Mellitus, which occurs due to uncontrolled blood glucose levels. Patients with a history of Diabetes Mellitus are susceptible to wounds, especially on the feet, and are difficult to heal, leading to infection. Bacteria identified as causing infection in diabetic ulcers include gram-positive bacteria such as Staphylococcus aureus and Staphylococcus epidermidis. The purpose of this study was to determine the antibacterial activity of Tinospora cordifolia (Willd.) Miers leaf gel against Staphylococcus aureus bacteria, which are the bacteria that cause infections in diabetic ulcers. The method used was to measure the area of ​​the inhibition zone formed on NA media that had grown bacteria, using the well method, then added the gel preparation of Tinospora cordifolia leaf extract with each concentration of 10%, 20% and 30%. Previously, the gel preparation had been evaluated by several tests such as organoleptic tests, homogeneity, adhesiveness, spreadability and pH. The results of the study obtained antibacterial activity testing at each concentration have antibacterial activity with each category being moderate and very strong. The very strong category was obtained at a concentration of 30% with an average inhibition zone obtained 15,64 mm, while at a concentration of 10%, 20% were included in the moderate category with a concentration obtained 9,75, and 10,28 mm. The conclusion of this study is that the gel of brotowali leaf extract (Tinospora cordifolia (Willd.) has antibacterial activity against one of the bacteria that causes diabetic ulcer infections, namely Staphylococcus epidermidis.